Sócio e consumidor: uma análise da relação jurídica dos associados ao cooperativismo de crédito - Cabral, Ana Guarabira de Lima (2020)
The main objective of this research is to ascertain the legal nature of relations between cooperative and credit cooperative to delimit the legislation incident in the event of conflicts among associates and society. The understanding of the issue involves the historical and legislative evolution of the cooperative movement, mainly its founding principles, as well as the timely analysis of the subjects participating in this corporate species that obeys the rule of its own, in addition to the necessary comparison between the functioning and operationalization of credit cooperative with the Banking system. The legal antinomy between the definition of cooperative activities and services for consumerist purposes requires verification of the interpretation methods available in the planning for the resolution of normative conflicts. The Superior Courts have understood that the Consumer Protection Code should be applied to credit cooperatives because they are part of the National Financial System, but their decisions did not effect the necessary normative compatibility in divergent aspects between the Cooperative Law and the Consumer Protection Code. The chronology of the involved laws, the constitutional hierarchy, the Law of Introduction to the Standards of the Brazilian Law, and mainly the theory of "dialogue of sources" constitute the way to the present research. This work is, thus, a theoretical, exploratory and bibliographic research based on a qualitative analysis of the fundamentals that aim to verify the applicability of the Consumer Protection Code to the relationships arising from the financial cooperative.